Perencanaan Ulang Tata Letak Area Produksi Mesin Packaging Menggunakan Metode Activity Relationship Chart dan Corelap - Fahmi Amirulloh; Atikha Sidhi Cahyana (Physical Sciences, Life Science and Engineering, 2026)
PT. Nobelindo is a company specializing in the manufacturing of processing and packaging machines tailored to customer needs. To meet customer demands, efficient processing equipment is essential to support material handling. One way to enhance material handling is through facility layout planning. The current facility layout is considered inefficient, as the distance workers must travel to the warehouse is too far, requiring each department to make 2-4 trips per day, with a total material handling distance of 110 meters. This study aims to redesign the facility layout to optimize the production flow by considering the flow of production and distances between production areas to achieve better efficiency using the Activity Relationship Chart and Corelap methods. The results show a total material handling distance of 59 meters, achieving an efficiency improvement of 46.3%. Therefore, this redesigned facility layout can serve as an alternative for PT. Nobelindo to optimize material handling processes.